A randomised controlled trial of small particle inhaled steroids in refractory eosinophilic asthma (SPIRA). Issue 6 (9th April 2015) - Hodgson, David; Anderson, John; Reynolds, Catherine; Meakin, Garry; Bailey, Helen; Pavord, Ian; Shaw, Dominick; Harrison, Tim
Abstract : Background: Some patients with refractory asthma have evidence of uncontrolled eosinophilic inflammation in the distal airways. While traditional formulations of inhaled steroids settle predominantly in the large airways, newer formulations with an extra-fine particle size have a more peripheral pattern of deposition. Specifically treating distal airway inflammation may improve asthma control. Methods: 30 patients with refractory asthma despite high dose inhaled corticosteroids were identified as having persistent airway eosinophilia. Following 2 weeks of prednisolone 30 mg, patients demonstrating an improvement in asthma control were randomised to receive either ciclesonide 320 µg twice daily or placebo in addition to usual maintenance therapy for 8 weeks. The primary outcome measure was sputum eosinophil count at week 8. Alveolar nitric oxide was measured as a marker of distal airway inflammation. Results: There was continued suppression of differential sputum eosinophil counts with ciclesonide (median 2.3%) but not placebo (median 4.5%) though the between-group difference was not significant. When patients who had changed their maintenance prednisolone dose during the trial were excluded the difference between groups was significant (1.4% vs 4.5%, p=0.028). Though alveolar nitric oxide decreased with ciclesonide the value did not reach statistical significance. Conclusions: These data demonstrate that patients with ongoing eosinophilic inflammation are not truly refractory, and that suppression of airway eosinophilia may be maintained with additional inhaled corticosteroid. Further work is needed with a focus on patient-orientated outcome measures such as exacerbation rate, with additional tests of small airway function. Trial registration number: NCT01171365. Protocol available at http://www.clinicaltrials.gov .